Review of an incident at a petrochemical plant - ’L Razi Ahmadun, Fakhru; Shalu, Ibrahim M.; Said Aini, Mat (Emerald, 2003)
Major hazard installations (MHIs) are dealing with hazardous substances which exceed the threshold quantity. MHIs are characterized by tight coupling and high complexity. Due to their complexity, MHIs require well trained managers who have good experience at all levels to manage the operations successfully. The managements of major hazard installations play a vital role in the success or failure of their installation. The world has witnessed many incidents in major hazard installations due to failure of the management at all levels. This paper summarizes in brief the management errors for several incidents which occurred worldwide. Also, the paper reviews the management errors which led to an incident at a petrochemical plant in East Malaysia.